Identification of Marine Fish Taxa by Linear Discriminant Analysis of Reflection Spectra in the Near-Infrared Region - Novikov V.; Baryshnikov A.; Rysakova K.; Shumskaya N.; Uzbekova O. (Техника и технология пищевых производств)
Introduction. Near-infrared (NIR) spectroscopy is a modern instrumental method for the quantitative and qualitative analysis of various objects. The method for analyzing the NIR spectra of diffuse reflection was successfully used to identify plant and animal species, drugs, etc. The issue of identifying objects of marine fishery is currently extremely important for modern fisheries, environmental monitoring, and identifying counterfeit products. The research objective was to identify the fish taxa using the discriminant analysis of reflection in the NIR region. Study objects and methods. The research featured 25 dried and defatted muscle tissue samples taken from different species of marine fish caught in the North Fishing Basin. The spectra were measured using a Fourier IR-spectrophotometer Shimadzu IRTracer-100 with a diffuse reflection measuring instrument. Measurements were carried out in the range from 700 to 7,000 cm–1. Mathematical processing of the spectra was performed using the MagicPlot Pro program ver. 2.9 (Magicplot Systems, LLC), while the statistical program IBM SPSS Statistics ver. 25 (IBM Corp., USA) was exploited to perform the linear discriminant analysis. Results and discussion. The spectra of diffuse reflection of NIR radiation were measured for 25 samples of marine fish species of different taxa caught in the North Fishing Basin. The range of 3,700 to 6,700 cm–1 was selected to assess the proximity of spectra in linear discriminant analysis. In this range, the team identified 19 spectral peaks, which made a significant contribution to canonical discriminatory functions. The resulting canonical discriminatory functions made it possible to divide the objects into eight nonoverlapping groups corresponding to each biological group of the fish. The analysis was based on a comparison of Mahalanobis distance between the group centroids and the NIR spectra of each studied fish species. The minimum Mahalanobis distance between the nearest groups was statistically significant. Conclusion. The research proved the possibility of taxonomic identification of marine fish based on measuring the spectral characteristics of their muscle tissue proteins in the range of 3,700 to 6,700 cm–1 of near-infrared region and classification by linear discriminant analysis.